The effect of training towards employee performance: An evidence from a public university in Malaysia - Nor Shamsida, Mohd Shahidan Lee; Suhaidah, Hussain; Razalina, Abdul Rashid; Mahadir, Abdul Raffar; Norhana, Mohd Aripin (Penerbit Universiti Malaysia Pahang, 2023)
Employees are the true determinant of the success or competency of an organization. An adequately trained workforce is important to ensure the workplace has the right and valuable employees. Employees in the education sector need the training to improve their performance as they face limitations or challenges to be creative in completing a task. Despite the increasing effects on the training of organizational employees by organizations, there is still limited literature on human resource development issues in developing countries. The study is focused on the effect of training towards employee performance in a public university in Malaysia. Consequently, all the necessary data were collected from primary sources using questionnaires from 244 respondents. This study employed a quantitative approach and found that induction, technical, and soft skill training positively influence employee performance in the case company. In addition, the study recommended future research in training and development strategies, assisting the employees in understanding the relevance of training towards employee performance, monitoring the performance to ensure employees are on track to achieve the best performance, growing and maintaining the employee’s performance to ensure the organization and personal goal can be achieved.